The Relationship Between the Contact Force at the Ankle Hook and the Hamstring Muscle Force During the Nordic Hamstring Exercise - Ruan, Mianfang; Li, Li; Zhu, Weiping; Huang, Tianchen; Wu, Xie (Frontiers in Physiology, 2021)
A novel device has been developed to assess eccentric hamstring strength during the Nordic hamstring exercise (NHE) by measuring the contact force at the ankle joint hook (brace). The purpose of this study was to determine the correlation between the force measured at the ankle joint brace and the hamstring force estimated by a low extremity model. Thirteen male college sprinters were recruited to perform NHE on an instrumented device Nordbord (Vald Performance, Australia). Contact forces were measured at a sampling rate of 50 Hz at the hooks using the uniaxial load cells. 3D kinematics were measured simultaneously at a sampling rate of 200 Hz using a 16-camera motion analysis system (Vicon Motion Analysis, Oxford, United Kingdom) during the NHE. The data were processed with Visual 3D (C-Motion, Germantown, MD, USA) and OpenSim (NCSRR, Stanford, CA, USA) to calculate the knee joint center's coordinates and hamstring moment arms during NHE. A static low extremity model was built to estimate the hamstring force during NHE. We have observed a significant but not very high correlation (r2=0.58) between peak hamstring force and the ankle joint's peak contact force. The peak contact force measured at the ankle joint can only explain a little more than half of the variations in peak hamstring muscle forces during NHE. Caution must be exercised when assessing the eccentric hamstring strength using the ankle joint's contact force during NHE.